Clear separation and combination of synchronization constraint for concurrent object oriented programming - Yasutake, Y.; Masuyama, Y.; Oda, K.; Yoshida, T. (17th International Conference on Advanced Information Networking and Applications, 2003)
This paper presents a language framework for a concurrent description and an implementation of a synchronization mechanism in distributed object-oriented computation. Some concurrent object-oriented languages are considered to be constructed from a user-defined function and a synchronization constraint. We propose the language for the synchronization constraint, which allows to define mutual exclusion and conditional synchronization by using declarative notations. The synchronization constraint is separated from user-defined functions, and the relation between them is described in the binding code. The binding mechanism reduces the dependency between them and contributes to code reuse. This framework makes it is easy for programmers to understand and describe the use-defined functions and synchronization constraints independently. The implementation of the synchronization mechanism is based on a reconfigurable object model that we are developing. The user-defined function and synchronization mechanism are implemented as its own separated module in the single object. Then the synchronization mechanism has flexibility and preserves the concept of object-orientation.